B-lynch suture in the management of uterine atony during caesarean section section - C., Sudha H.; Pairu, Jaganathan; ., Kamalakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Third stage of labour is still the “sword of Damocle’s” hanging above an obstetrician , inspite of today’s advanced technologies and personal care .The importance in the management of this deadly stage lies in the anticipation of complications and being quick enough to treat them timely. Hence in such scenarios, B-lynch suture is most popular method in treatment of uterine atony during caesarean section. The objective is to study and evaluate the cases in which the B-Lynch suture was used to treat the uterine atony during caesarean section. Methods: A prospective randomized study consisting of 50 women with high risk factors for atonic pph during caesarean section were included as study group patients were subjected to B-Lynch suture application when conventional drugs failed to control PPH. Blood loss was measured using a measuring jar. The fall in Hb% and the need for blood transfusion, and the need for hysterectomy as a last resort to save the life was evaluated. Results: The average blood loss was 1490 ml and the majority of patients had reduction in Hb% from 1.1-1.5 gm% (52%), 36% of the patients did not receive any blood transfusion after B-Lynch suture, and in 80% of cases hysterectomy was avoided. Conclusions: Our study shows cases treated with B-Lynch procedure showed that it is an effective method of containing pph. It has the advantage of being applied easily and safely. It should be attempted when conservative management fails and before any radical surgery is considered.